1988
DOI: 10.1093/carcin/9.10.1849
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the oncogenes mil and ras abolishes the in vivo differentiation of mammary epithelial cells

Abstract: Three carcinoma-associated oncogenes, two of which have been strongly implicated in human mammary tumorigenesis, have been introduced into a novel mouse mammary epithelial cell line, EF43, that retains many differentiated functions. The effect of oncogene expression upon classical transformation parameters as well as parameters specific for mammary epithelial cells such as growth in three-dimensional collagen matrices and the ability to repopulate the cleared mammary fat pad and to form alveolar structures in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Id-1-expressing SCp2 cells did not grow in an anchorage-independent manner and did not form detectable tumors in nude mice. Thus, Id-1 differs from oncogenes such as v-Ha-ras, which converts mouse mammary epithelial cells into invasive but also tumorigenic cells (13). Furthermore, Id-1 did not induce an invasive phenotype by converting cells to a stromal or mesenchymal phenotype.…”
Section: Discussionmentioning
confidence: 91%
“…Id-1-expressing SCp2 cells did not grow in an anchorage-independent manner and did not form detectable tumors in nude mice. Thus, Id-1 differs from oncogenes such as v-Ha-ras, which converts mouse mammary epithelial cells into invasive but also tumorigenic cells (13). Furthermore, Id-1 did not induce an invasive phenotype by converting cells to a stromal or mesenchymal phenotype.…”
Section: Discussionmentioning
confidence: 91%
“…We used electroporation as the mode of gene transfer into the MMEC. Because most epithelial cells are poorly transfectable by the conventional calcium phosphate technique (Redmond et al, 1988), many investigators have used retrovirus-mediated gene transfer to transfect epithelial cells (Gunzberg et al, 1988;Redmond et al, 1988;Ball et al, 1988). We have demonstrated high-efficiency, stable gene transfer by electroporation into a variety of cell types, including epidermal keratinocytes (Reiss et al, 1986), bone marrow cells ), neuronal cells (Ito et al, 1989), as well as many different primary cell types (Narayanan, unpublished observations).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, upregulation of normal Ras activity by receptor tyrosine kinases (RTK), such as the EGF receptor family, is a major focus for breast cancer research 23, 30 . Introduction of activated H-Ras into certain mouse or human breast epithelial cells results in acquisition of a transformed phenotype in vitro (such as increased anchorage independent growth) and in vivo , as shown by the ability to form tumors in nude mice 10, 15, 48 . In addition, a large number of clinical studies have demonstrated overexpression of Ras in breast cancers 12, 34, 64 .…”
Section: Discussionmentioning
confidence: 99%